Islam dan Perubahan Iklim Global: Studi Transmisi Hadis Era Kontemporer - Rafi Rasyad Kadarusman; Yeni Huriani; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the transmission of hadith about cleanliness in responding to global climate change. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of dirayah and riwayah hadith, while the material object is the hadith about cleanliness in Muslim history No. 328 in the context of global climate change. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for justification for practicing Islam. This study concludes that the hadith narrated by Muslim No. 328 about cleanliness can be transmitted in the contemporary era to be involved in responding to increasingly extreme global climate change.